Northeastern Patagonian Glacier Advances (43°S) Reflect Northward Migration of the Southern Westerlies Towards the End of the Last Glaciation - Leger, Tancrède P. M.; Hein, Andrew S.; Goldberg, Daniel; Schimmelpfennig, Irene; Van Wyk de Vries, Maximillian S.; Bingham, Robert G.; , ASTER Team; Aumaitre, Georges (Frontiers in Earth Science, 2021)
The last glacial termination was a key event during Earth’s Quaternary history that was associated with rapid, high-magnitude environmental and climatic change. Identifying its trigger mechanisms is critical for understanding Earth’s modern climate system over millennial timescales. It has been proposed that latitudinal shifts of the Southern Hemisphere Westerly Wind belt and the coupled Subtropical Front are important components of the changes leading to global deglaciation, making them essential to investigate and reconstruct empirically. The Patagonian Andes are part of the only continental landmass that fully intersects the Southern Westerly Winds, and thus present an opportunity to study their former latitudinal migrations through time and to constrain southern mid-latitude palaeo-climates. Here we use a combination of geomorphological mapping, terrestrial cosmogenic nuclide exposure dating and glacial numerical modelling to reconstruct the late-Last Glacial Maximum (LGM) behaviour and surface mass balance of two mountain glaciers of northeastern Patagonia (43°S, 71°W), the El Loro and Río Comisario palaeo-glaciers. In both valleys, we find geomorphological evidence of glacier advances that occurred after the retreat of the main ice-sheet outlet glacier from its LGM margins. We date the outermost moraine in the El Loro valley to 18.0 ± 1.15 ka. Moreover, a series of moraine-matching simulations were run for both glaciers using a spatially-distributed ice-flow model coupled with a positive degree-day surface mass balance parameterisation. Following a correction for cumulative local surface uplift resulting from glacial isostatic adjustment since ~18 ka, which we estimate to be ~130 m, the glacier model suggests that regional mean annual temperatures were between 1.9 °C and 2.8 °C lower than present at around 18.0 ± 1.15 ka, while precipitation was between ~50% and ~380% higher than today. Our findings support the proposed equatorward migration of the precipitation-bearing Southern Westerly Wind belt towards the end of the LGM, between ~19.5 and ~18 ka, which caused more humid conditions towards the eastern margins of the northern Patagonian Ice Sheet a few centuries ahead of widespread deglaciation across the cordillera.